Bioactivity of Essential Oils from Patagonian Wild Plants: Acaricidal and Insecticidal Effects on Varroa destructor and Apis mellifera - Manzo, Rosa M. (2025)
Varroa destructor represents a major threat to honeybee colonies worldwide, prompting the search for alternative organic acaricides. This study evaluated the biological activity of essential oils extracted from three Patagonian wild plants—Adesmia boronioides, Dysphania multifida, and Senecio filaginoides—on both V. destructor and Apis mellifera. Chemical analysis revealed that A. boronioides oil was dominated by esquelenone (34.49%), D. multifida by ascaridole (34.87%), and S. filaginoides by α-pinene (40.87%). All essential oils exhibited acaricidal activity, with D. multifida showing the lowest LC50 against V. destructor (1.1 µL/mL at 24 h). Toxicity assays on adult bees indicated that A. boronioides and D. multifida significantly reduced bee survival, whereas S. filaginoides did not appear to cause significant mortality (LC50 = 139.5 µL/mL). Repellency tests for A. boronioides and D. multifida showed significant mite repellence. Larval assays revealed a high survival rate under S. filaginoides treatment (survival rate > 80.24%), in contrast to the reduced viability observed with the other oils. The high selectivity index of S. filaginoides underscores its potential as a selective and safe botanical acaricide. Moreover, its LC50 decreased over time, suggesting a residual acaricidal effect. These findings support S. filaginoides as a promising candidate for sustainable V. destructor control.